Correlation between tumor budding, microvascular density, and β-catenin expression in colorectal carcinoma. Issue 1 (July 2016) - El Sheikh, Samar A.; Bassam, Amira M.; Ibrahim, Heba A.
Abstract : Background: Colorectal cancer is one of the leading causes of cancer death worldwide. Therefore, identification of the clinicopathological prognostic factors associated with tumor growth, invasion, and metastasis is critical to develop proper therapeutic interventions. Tumor budding is a high-grade undifferentiated component of a tumor at the leading invasive edge that appears as small clusters (<5) or single infiltrating cancer cells. Patients and methods: The current study included 50 cases of colorectal carcinoma studied histologically for tumor budding and immunohistochemically for β-catenin expression and microvascular density (MVD) with CD34. Results: Tumor budding was observed in 62% of cases, and it showed a statistically significant correlation with advanced Dukes' stage, positive lymph node metastasis, and increasing stage of lymph node metastasis. β-Catenin expression was positive in 34% of cases. There was no statistical relationship between β-catenin expression and different clinicopathological findings, except when associated with concomitant budding and lymph node metastasis. MVD showed significant correlation only with the sex of the patient but no correlation with tumor budding or β-catenin expression. Conclusion: This study suggests that tumor budding might play a role in the ability of colon cancer cells to invade locally and metastasize and thus may be used as a prognostic marker to predict poor outcome in patients; hence a scoring system for pathological reporting of tumor budding may be beneficial. Our study also supports a potential role for β-catenin in the process of budding and metastasis. It will be necessary to carry out similar studies on a larger sample size to predict the possible prognostic significance of β-catenin and MVD.